Viking warrior women? Reassessing Birka chamber grave Bj.581. (18th February 2019) - Price, Neil; Hedenstierna-Jonson, Charlotte; Zachrisson, Torun; Kjellström, Anna; Storå, Jan; Krzewińska, Maja; Günther, Torsten; Sobrado, Verónica; Jakobsson, Mattias; Götherström, Anders
Abstract: Abstract : The warrior woman has long been part of the Viking image, with a pedigree that extends from the Valkyries of Old Norse prose and poetry to modern media entertainment. Until recently, however, actual Viking Age evidence for such individuals has been sparse. This article addresses research showing that the individual buried at Birka in an 'archetypal' high-status warrior grave—always assumed to be male since its excavation in 1878—is, in fact, biologically female. Publication, in 2017, of the genomic data led to unprecedented public debate about this individual. Here, the authors address in detail the interpretation of the burial, discussing source-critical issues and parallels.